Japan - Yamamoto, M. Y.-Y. (Comparative elite sport development. Systems, structures and public policy, 2025)
Recent Japanese sport policy has been strongly influenced by the policy debates prior to the unsuccessful bid for the 2016 Tokyo Olympic and Paralympic Games (in 2007) as well as by the successful bid for the Tokyo 2020 Games (awarded in 2013). Both bids and, in particular, the granting of the Tokyo 2020 Games have affected the development of sport policy and overall government policy. It is also important to note that the global COVID-19 pandemic, which inevitably led to the postponement of Tokyo 2020, the first time a Games had been postponed in the 125 years of the Olympics, to 2021, influenced the general public's view on sport and health (or healthy lifestyle/well-being). Japanese elite sport policy has developed significantly since 2000 and has applied a structural approach and focused more on sustainability of high-performance success in the post-Tokyo 2020 phase.